Strategi Peningkatan Minat Baca di Rumah Literasi: Analisis Faktor Pendukung dan Penghambat - Hanifah Noviandari (Elsalima (Salam Institute), 2024)
This study aims to identify supporting and inhibiting factors, formulate strategies to enhance reading interest and evaluate the effectiveness of the programs at Rumah Literasi Desa Sidoharjo, Ponorogo. The research uses a descriptive approach with interviews, observations, and documentation. The results show that the main supporting factors include adequate facilities, active participation of managers, and community awareness of the importance of reading. Inhibiting factors include limited time, access to technology, and minimal promotion. Strategies for improvement include increasing socialization through social media, brochures, and direct outreach, adjusting activity schedules, and developing relevant programs, such as writing workshops and book discussions. Overall, the implemented programs are effective in increasing community reading interest but require improvements in program quality and time flexibility. Rumah Literasi Desa Sidoharjo has great potential to contribute to improving reading interest through sustained efforts and more effective strategies.